2012
DOI: 10.1093/bja/aer461
|View full text |Cite
|
Sign up to set email alerts
|

Management of the dialysis patient in general intensive care

Abstract: The incidence of end-stage renal disease (ESRD) is rising and represents an important group of patients admitted to intensive care units (ICU). ESRD patients have significant co-morbidities and specific medical requirements. Renal replacement therapy (RRT), cardiovascular disease, disorders of electrolytes, drug metabolism, and sepsis are discussed. This review provides a practical approach to problems specific to the ESRD patient and common problems on ICU that require special consideration in ESRD patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 103 publications
1
20
0
1
Order By: Relevance
“…The maladies of our ICU maintenance dialysis patients with a high burden of coexisting diseases mirror the acute illnesses commonly encountered in non-renal ICU patients. We observed short-term and mid-term mortality rates well within published ranges (5,16).…”
Section: Dialysis Dosing In Maintenance Hd Patients 471supporting
confidence: 84%
“…The maladies of our ICU maintenance dialysis patients with a high burden of coexisting diseases mirror the acute illnesses commonly encountered in non-renal ICU patients. We observed short-term and mid-term mortality rates well within published ranges (5,16).…”
Section: Dialysis Dosing In Maintenance Hd Patients 471supporting
confidence: 84%
“…Impaired renal function is a major risk factor for cardiovascular morbidity and mortality [14]. Several factors may contribute to the increased incidence of cardio-respiratory dysfunction in patients with ESRD, including left ventricular hypertrophy, rapid electrolyte shifts during dialysis, QT dispersion, sympathetic over-activity, and deposition of calcium-phosphate precipitants within arteries [14,15]. Acute pulmonary infections, perioperative volume overload, excessive inter-dialytic weight gain, and primary cardiac events may also contribute to respiratory failure in patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of hepatic failure in our patients may be explained by the higher incidence of liver cirrhosis in these patients compared with those without ESRD. The impairment of renal elimination of hypnotic and sedative agents given perioperatively in patients with ESRD [14] may explain the high occurrence of neurological failure in these patients. Interestingly, we found that hematologic failure occurred up to 4 times more frequently in patients with ESRD than in those without.…”
Section: Discussionmentioning
confidence: 99%
“…The management of the ESRD patient on ICU is beyond the scope of this article and is detailed elsewhere in the literature. 37…”
Section: Causes Of Admissionmentioning
confidence: 99%